The ability of the Ni/Al2O3 catalyst in the CO2 methanation process in﻿ terms of variations in CO2 flow rate and catalyst - Sultan Parega; Robert Junaidi; Didiek Hari Nugroho; Helda Niawanti (Konversi, 2024)
Carbon dioxide (CO2) is one of the biggest contributors to the greenhouse effect. Based on International Energy Agency (IEA) data, global emissions of carbon dioxide (CO2) from burning energy and industrial activities will reach 36.8 billion tons in 2022. The increase in emissions in 2022 will mainly come from burning coal and fuel oil (Fuel Oil). Carbon dioxide emissions from coal rose 1.6% while fuel oil emissions increased 2.5%. One effort to reduce carbon dioxide emissions is to convert carbon dioxide into methane gas (CH4) which can be used as fuel. This research aims to produce methane gas from carbon dioxide using Ni/Al2O3 catalyst treatment and varying CO2 flow rates. In this research, CO2 was used as a raw material with a Ni/Al2O3 catalyst and Zn metal. Based on the research results, the highest conversion yield of methane gas was 49.23% with a variation of 0.05 L/minute with Ni_R4 catalyst treatment